Correlation between Apolipoprotein B (Apob) Level and Non Alcoholic Fatty Liver in Type 2 Diabetes Mellitus with Metabolic Syndrome - Tejo Nugroho; Tantoro Harmono; Tri Yuli Pramana; Sugiarto Sugiarto (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2011)
Background: Non-alcoholic fatty liver disease (NAFLD) is a liver disorder commonly found in the majority of patients with metabolic risk factors, such as obesity and type 2 diabetes. Apolipoprotein B (apoB) is the moiety of low density lipoprotein (LDL) and clinical interest that provides a relative accurate estimation of circulating LDL particle. The aim of this study was to know the relationship between apoB level and occurrence of fatty liver in type 2 diabetes mellitus (DM) with metabolic syndrome. Method: A cross sectional study was conducted in patients suffered from type 2 DM with metabolic syndrome at Internal Medicine Outpatient Clinic in Moewardi Hospital Surakarta between April and May 2011. Thirty two patients with type 2 DM and metabolic syndrome were enrolled to this study and categorized into two groups; consisting of 16 patients with fatty liver and 16 patients without fatty liver. Student t-test was used in the analysis of this study. Results: Of 32 patients who fulfilled this study criteria, patients type 2 diabetes mellitus and metabolic syndrome with non-alcoholic fatty liver diseases (NAFLD) had higher apoB level than patients type 2 diabetes mellitus and metabolic syndrome without NAFLD (p = 0.013). Conclusion: NAFLD group had significantly higher apoB level than without NAFLD group in type 2 DM with metabolic syndrome patients. Keywords: apolipoprotein B, non-alcoholic fatty liver disease, type 2 DM, metabolic syndrome